Cloning and comparison of ten gene sequences of a Chilean H. pylori strain with other H. pylori strains revealed higher variability for VacA and CagA virulence factors - MÜLLER,ILSE (Sociedad de Biología de Chile, 2002)
We have cloned and sequenced ten Helicobacter pylori genes from a Chilean strain (CH-CTX1) including: a cytotoxin VacA fragment, a CagA fragment (A17), a species-specific protein (TsaA), urease subunits (UreA, UreB), a flagellin subunit (FlaB), heat shock proteins (HspA and HspB), adhesin (HpaA) and a lipoprotein (Lpp20). We compared their deduced amino acid sequences with the corresponding sequences from three unrelated H. pylori strains, including fully sequenced strains 26695(UK) and J99(USA), and found that eight of them (UreA, UreB, FlaB, HspA, HspB, Lpp20, TsaA and HpaA) presented more than 97.3% identity. In contrast, VacA partial sequence showed lower identity values (93.2 - 94.9%). Moreover, we found major differences in the A17 region respect to the number and arrangement of the internal repeated elements when sequences from different strains were aligned. The A17 regions from strains CH-CTX1 and 26695 are very similar (91.8% identity) but lacked 6 repeated elements when compared to the Australian strains ATCC 43526 and NCTC 11637. The CCUG 17874 A17 region showed the largest deletion involving 9 repeats. A17 size differences between strains CCUG 17874 and CH-CTX1 were verified by PCR and polypeptide size. Such differences may explain variations in virulence among H. pylori strains as well as diversity in serum immunoreactivity.